2021
DOI: 10.3390/su132414007
|View full text |Cite
|
Sign up to set email alerts
|

Biomethane from Manure, Agricultural Residues and Biowaste—GHG Mitigation Potential from Residue-Based Biomethane in the European Transport Sector

Abstract: Biomethane from manure, agricultural residues, and biowaste has been prioritized by many energy strategies as a sustainable way to decrease greenhouse gas (GHG) emissions in the transport sector. The technology is regarded as mature; however, its implementation is still at an early stage. At EU level, there are currently two major instruments relevant for promoting the production of biomethane from waste and residues and which are likely to contribute to unlocking unused GHG mitigation potentials: the Renewabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The calculation of greenhouse gases was carried out based on Directive 2018/2001/EU (REDII) [39], [40]. This directive is a continuation of REDI 2009, which sets out methods for controlling the sustainable and ecological production of biofuels.…”
Section: Ghg Savings Calculationmentioning
confidence: 99%
“…The calculation of greenhouse gases was carried out based on Directive 2018/2001/EU (REDII) [39], [40]. This directive is a continuation of REDI 2009, which sets out methods for controlling the sustainable and ecological production of biofuels.…”
Section: Ghg Savings Calculationmentioning
confidence: 99%
“…In order to decrease GHG emissions in a sustainable way in the transport sector, production of biomethane from manure, agricultural residues, and biowaste can have a profound impact [39]. This aspect of biomass application was considered in the publication by Oehmichen et al [40] by assessing the market. The study showed that different advanced biofuel pathways have significantly different GHG mitigation costs.…”
Section: The Special Issuementioning
confidence: 99%
“…Germany also has 1900 agricultural digesters out of the 2429 currently existing in Europe [89]. However, only around 50% of the mobilisable technical biomass potential of animal manure is used for energy purposes in Germany [102]. Overall, the technical potential of biogas in the EU is estimated to be between 151-246 billion Nm 3 of biomethane from AD [89].…”
mentioning
confidence: 99%